Blood Eosinophil Count as a Predictive Biomarker of Chronic Obstructive Pulmonary Disease Exacerbation in a Real-World Setting - Moegi Komura; Tadashi Sato; Yohei Suzuki; Hitomi Yoshikawa; Naoko Arano Nitta; Mika Hayashi; Eriko Kuwasaki; Kimiko Horikoshi; Toshihiko Nishioki; Mikiko Mori; Yuzo Kodama; Shinichi Sasaki; et al. (Canadian Respiratory Journal)
Introduction. Chronic obstructive pulmonary disease (COPD) is the third leading cause of death, and COPD exacerbation worsens the prognosis. Eosinophilic airway inflammation is a COPD phenotype that causes COPD exacerbation and is correlated with peripheral blood eosinophil count. We analyzed real-world data of COPD patients to assess the risk factors of COPD exacerbation focusing on blood eosinophils. Materials and Methods. Patients with COPD who visited our hospital between January 1, 2018, and December 31, 2018, were recruited, and their background information, spirometry data, laboratory test results, and moderate-to-severe exacerbation events during the one-year follow-up period were collected from the electronic medical records and analyzed. The COPD exacerbation risk factors were assessed using univariate and multivariate logistic regression analyses. Results. Twenty-two of 271 (8.1%) patients experienced moderate-to-severe exacerbation. Patients with exacerbation showed worse pulmonary function, and we found that a high blood eosinophil count (≥350 cells/μL; p=0.014), low % FEV1 (<50%; p=0.002), increase in white blood cell (≥9000 cells/μL; p=0.039), and use of home oxygen therapy (p=0.005) were risk factors for future exacerbations. We also found a strong correlation between eosinophil count cut-offs and exacerbation risk (r = 0.89, p<0.001). On the other hand, there was no relation between exacerbation risk and inhalation therapy for COPD. Conclusion. In a real-world setting, peripheral blood eosinophil count could be a predictor of future COPD exacerbation.